ANALISIS FRAMING : BERITA PASCA DEBAT PERTAMA CALON PRESIDEN 2024 PADA SITUS MEDIA ONLINE - Amal, Ikrimatul; Hayati, Lena Sri; Kurniawati, Nia Kania; Gumelar, Rangga Galura (Mediakom : Jurnal Ilmu Komunikasi, 2024)
December 12 2023 is a very important moment for presidential and vice presidential candidate pairs because on December 12 the holding of the first debate for presidential candidates is the core of a series of presidential candidates' campaign programs ahead of the 2024 election. In reporting the presidential candidates, discussions emerged regarding media independence. Several political figures who also have power as owners of mass media use and exploit mass media to secure their political interests. The content of the media tends to reflect the political interests of the media owner. This is contrary to the true essence of the media, which should play a role in maintaining its ideal function. Therefore, this research aims to examine how media framing in media alignments in the presidential and vice presidential election process in 2024 is due to each candidate having their own supporter. has power over certain media. This research method uses Gamson and Modigliani's framing analysis of news after the presidential candidate debate on December 12 2023 by taking the objects analyzed in the form of online media Viva.co.id, SINDOnews.com and Metrotvnews.com. The results of this research can be seen from how each of these media favors their candidate pairs by creating positive headline narratives.